基于蒙特卡罗方法的双臂机器人工作空间分析 - 周律; 周昱明; 汪亮; 朱金龙 (Jixie chuandong)
The workspace of dual-arm robot is the research hotspot and difficulty in robot industry,taking the self-developed dual-arm robot as the research object,the D-H coordinate system is established and the kinematics equation is work out.According to the Monte Carlo method and the extreme value theory,using Matlab simulation software,its workspace is solved.The practicability and universality of Monte Carlo method is proved again.It provides a theoretical basis for subsequent robot trajectory planning and control research.